Implementasi Integral dalam Bidang Ekonomi di Indonesia - Ramadhanty, Desfi; Kustiawati, Dedek; Fakhrezi, Ficky; Rizki Dalimunte, Mutiara (Jurnal Etnik: Ekonomi-Teknik, 2023)
The implementation of integral in the field of economics in Indonesia plays a very important role in helping the government and companies make the right and wise decisions. By using integral methods, the government and companies can determine the point of production efficiency, estimate the optimal production level, and determine the total cost needed to reach that production level. The method used in this study is a literature review. A literature review is one of the research methods that relies on existing documents. Cost is the amount of money a company spends on its production activities and is expressed as C or TC (Total Cost). The revenue function, also called the income or sales function, is represented by R or TR (Total Revenue). The utility function explains the level of satisfaction that consumers receive from a good or service. The production function describes the relationship between output and production factors. The producer's surplus is the difference between revenue and the minimum benefit received by the producer. Consumption is an economic action taken to meet needs using goods or services. The savings function shows the relationship between savings and income.